Mie Gacoan Consumer Loyalty: The Influence Halal Certification, Quality Product, Taste Quality and Location - Nita Puspita; Norma Rosyidah (ASEAN Journal of Halal Study, 2026)
The rapid growth of Indonesia's culinary industry has intensified competition among spicy noodle brands, with halal certification, product quality, taste satisfaction, and location emerging as factors that may shape consumer loyalty among student consumers. This study examines the influence of these four factors on consumer loyalty to Mie Gacoan among students in Sidoarjo. A quantitative approach was used, with data collected through questionnaires distributed to 100 students who had purchased Mie Gacoan products, selected via purposive sampling, and analysed using validity, reliability, t-tests, and F-tests with SPSS version 27. The results show that taste satisfaction and location have a positive and significant influence on consumer loyalty, while halal certification has a significant but negative influence, and product quality has a negative and non-significant influence. All four variables together significantly affect consumer loyalty, explaining 55.3% of its variance. These findings suggest that loyalty among student consumers is shaped primarily by taste satisfaction and accessibility of location, with the role of halal certification requiring further investigation given its unexpected direction. Mie Gacoan is encouraged to maintain taste consistency and location accessibility while reassessing how halal certification is communicated to consumers.